1999
DOI: 10.1152/ajpendo.1999.276.2.e223
|View full text |Cite
|
Sign up to set email alerts
|

The endocrine secretion of mammalian digestive enzymes by exocrine glands

Abstract: The exocrine pancreas and certain salivary glands of mammals secrete a variety of enzymes into the gastrointestinal tract, where they digest food. The same glands also release these enzymes into the bloodstream. This latter process has commonly been assumed to occur solely as the result of a pathological condition or as an inadvertent by-product of exocrine secretion due to the leakage of trace quantities of the enzymes into blood. However, a variety of evidence suggests that the endocrine secretion of digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 47 publications
1
54
0
2
Order By: Relevance
“…Conversely, only a modest amount of hPTH was found in the saliva of these mice, that is, hPTH secretion was primarily in an endocrine direction in mouse salivary glands. Although less commonly considered, secretion into the bloodstream from the salivary glands is well described and occurs via illdefined basolateral secretory pathways (Kagami et al, 1996;Baum et al, 1999;Isenman et al, 1999;Gorr et al, 2005). The immunofluorescent staining of transduced mouse glands revealed a significant accumulation of hPTH on the basolateral side of parenchymal cells, consistent with the hypothe-…”
Section: Figsupporting
confidence: 66%
See 1 more Smart Citation
“…Conversely, only a modest amount of hPTH was found in the saliva of these mice, that is, hPTH secretion was primarily in an endocrine direction in mouse salivary glands. Although less commonly considered, secretion into the bloodstream from the salivary glands is well described and occurs via illdefined basolateral secretory pathways (Kagami et al, 1996;Baum et al, 1999;Isenman et al, 1999;Gorr et al, 2005). The immunofluorescent staining of transduced mouse glands revealed a significant accumulation of hPTH on the basolateral side of parenchymal cells, consistent with the hypothe-…”
Section: Figsupporting
confidence: 66%
“…However, salivary glands can secrete exocrine and endocrine proteins to either the apical pole or the basolateral pole of the cells (Lawrence et al, 1977;Leonora et al, 1987;Baum et al, 1999;Isenman et al, 1999). Unfortunately, the direction of this secretion is not readily predictable for all transgenic proteins.…”
mentioning
confidence: 99%
“…Although it would seem surprising that a presumptive endocrine factor is strongly expressed in an exocrine gland, there have been numerous reports of other growth factors being expressed in salivary glands (15)(16)(17)(18)(19), and it has been shown that endocrine factors expressed after introduction of DNA into these glands are readily secreted into the bloodstream (20,21). Indeed, a body of opinion contends that salivary glands have a mixed exocrine and endocrine function (22)(23)(24). Similarly, we also saw expression in the lacrimal glands of newborn mice.…”
Section: Resultsmentioning
confidence: 99%
“…These lead to specific sorting routes for transgenic secretory proteins in an endocrine and exocrine manner [16]. For example, human growth hormone (hGH), which in the anterior pituitary gland is secreted into the bloodstream via the RSP, when expressed from an adenoviral vector delivered to rodent and miniature pig salivary glands, follows the tissue specific RSP, i.e., the exocrine route into saliva [17][18][19].…”
Section: Introductionmentioning
confidence: 99%